PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PASIEN BPJS KESEHATAN DI OPTIK KOTA PADANG - Febry Corina; Alvia Wesnita (Ensiklopedia of Journal, 2023)
In Indonesia, visual impairment has increased by 1.5% and is the highest compared to other Southeast Asian regional countries. The Indonesian government participates in realizing optimal eye health by issuing a BPJS health insurance policy. Realizing the implementation of optimal eye health in the form of optical facilities in collaboration with BPJS. The number of similar businesses is increasingly making a lot of competition, optical is expected to be able to provide good satisfaction to patients to maintain and improve the business itself. Patient satisfaction is obtained from many factors, one of which is service and product quality. discusses Service and Product Quality on BPJS Health Patient Satisfaction at Optics in Padang City. The research was conducted in two optics namely: Access Optic and Dian Optic in Padang City. This study aims to : (1) Find out about optical services on patient satisfaction of BPJS health at bach Optikal in Padang , (2) Know the quality of optical products on patient satisfaction from BPJS health at bach Optikal  in Padang, (3) Find out whether there is an influence of service and quality optical products on patient satisfaction BPJS health at Optics in Padang City. The research was carried out with a quantitative research type with a descriptive analytical research design with a cross sectional approach. Sampling was 50 BPJS health patients at Optics in Padang , consisting of 14 men and 36 women. The data collection of this research is got by a guestionaire. While the  technique of data collection was carried out by statistical tests using the SPSS data processor.Based on the results and discussion, it shows that, on average, 3.43 (86%) are satisfied with service to patient satisfaction BPJS health at Optics in Padang Full City, on average 3.41 (86%) are satisfied with product quality on patient satisfaction. BPJS health in Optics of Padang City, and there is a jointly significant influence (63.3%) that service and product quality have an effect on patient satisfaction of BPJS health in Optics of Padang City.